Effect of Grain Size and Distribution on Mechanical Behavior of Dune Sand - Amel Boudia; Abdelmadjid Berga (Civil Engineering Journal, 2021)
Sand is a major component of soils. It is widely used in manufacturing and construction. In geomechanics, one characterizes sand according to various aims. This paper investigates, for local sands, the effect of grain size and granular distribution on the mechanical behavior in terms of strength and stress-strain relationship. For this purpose, dune sands of the great Occidental Erg, from Algeria, are analyzed, according to the Mohr-Coulomb criterion. The study uses three kinds of sands. Every kind is divided into three sizes classes. Then, the experimental program conducts a set of direct shear tests, under various vertical stresses, using the small shear box (60 × 60 mm). The results show that the particle size and distribution have a direct effect on the mechanical behavior of the dune sand. Then, the dominant size class governs the natural sand behavior. Moreover, the peak shear strength increases as particle size increases. This indicates that there is an increase in peak friction angle with the increase of particles size and the sands consider as a purely cohesionless material. In addition, the experimental analysis shows that density and confinement stress is not sufficient to interpret the mechanical behavior. Indeed, mineralogy and surface state can influence the shear strength. These conclusions lead to the relevance of the sand genesis and the importance of the local materials thematic. Doi: 10.28991/cej-2021-03091730 Full Text: PDF